Performance study of UV micro-LEDs with AlGaN quantum dots and transparent tunnel junction - Yun-Cheng Hsu; Ching-Ho Tien; Yun-Han Chang; Sunanda Mitra; Sankesh Shetty; Sébastien Chenot; Mohamed Al Khalfioui; Hao-Chung Kuo; Chi-Wai Chow; Chia-Yen Huang; Julien Brault; Ray-Hua Horng (Next Nanotechnology)
It is well known that the size of deep ultraviolet (DUV) micro LED (μLEDs) decreases, although bandwidth improves, the optical power drops sharply, severely limiting the application of DUV μLEDs in optical communication. This study focused on the fabrication of DUV μLED with 10 μm × 10 μm dimenstion, utilizing molecular beam epitaxy (MBE) technology to grow AlGaN quantum dots (QD) and improve the stress in the quantum dot structure through stress engineering, thereby enhancing the light emission efficiency. To improve the ohmic contact in the p-type region, a tunneling structure is designed and incorporated, which helps increase carrier injection efficiency and further optimize the electrical performance of device. Additionally, by combining neutral particle beam etching (NBE) technology, the μLED is precisely processed, suppressing the processing damage that typically reduces light emission efficiency in conventional dry etching methods. Test results demonstrate that the integration of these technologies significantly improves the optoelectronic properties of the DUV μLED with 10 μm × 10 μm dimenstion, providing a reliable technical solution for DUV communication applications.